Enrichment of dementia caregiving relationships through psychosocial interventions: A scoping review - Hoel, Viktoria; Koh, Wei Qi; Sezgin, Duygu (Frontiers in Medicine, 2023)
Objectives: Enrichment, defined as “the process of endowing caregiving with meaning or pleasure for both the caregiver and care recipient” can support relationships between people living with dementia (PLWD) and their caregivers. This study aims to explore 1) the types of psychosocial interventions that may enrich relationships between dementia caregiving dyads, and 2) the components within these psychosocial interventions that may contribute to enrichment. Method: A scoping review was conducted based on the Joanna Briggs Institute framework. We operationalized and contextualized core elements from Cartwright and colleagues’ enrichment model, which was also used to guide the review. Five electronic databases were searched. Psychosocial intervention components contributing to enrichment were identified and grouped within each core element. Results: Thirty-four studies were included. Psychosocial interventions generating enrichment among dyads mainly involved supporting dyadic engagement in shared activities, carer education or training, or structural change to the environment around PLWD. Intervention components contributing to the enrichment of dyadic relationships were identified within ‘acquired symbolic meaning’, ‘performing activity’ and ‘fine tuning’. Dyadic communication support and skill-building were common contributors to enrichment. Conclusion: Our findings may inform the planning and development of interventions to enrich dyadic relationships in the context of dementia. In formal caregiving contexts, future interventions may consider dedicating space for relationships to build and grow through positive interactions. In informal caregiving contexts, existing relationships should be considered to better support dyads engage in positive interactions.